ECONOMIC DEVELOPMENT OF THE SERVICE SECTOR (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In this article, the socio-economic is more vital issue of increasing the labor potential through the effective use of labor resources in service enterprises, the manifestations and components for the labor potential, the criterias and indicators of increasing the efficiency of the use of labor resources are classified, and the main directions of the increase of the labor potential are researched.